The association between knowledge and implementation of good compounding practice among pharmacy practitioners at community pharmacies in Central Jakarta - Kurniawan, Adin Hakim; Safrina, Ulya; Yusmaniar, Yusmaniar (JURNAL ILMU KEFARMASIAN INDONESIA, 2024)
Drug compounding in community pharmacy is an important process in providing drugs according to patient needs. Poor compounding practices can pose serious health and safety risks. To improve the quality of compounds used in medicinal preparations, Pharmacists need to increase their knowledge and Good Compounding Practice (GCP). This study aimed to analyze the application knowledge of pharmacists regarding GCP of non-sterile preparations in Central Jakarta Regional Pharmacies. This type of research is observational research using cross-sectional descriptive methods. Data collection was carried out using a questionnaire distributed to 82 pharmacy practitioners working in the pharmacy community and using a structured questionnaire to evaluate the level of knowledge and implementation of GCP. The data analysis technique used is chi-square. Most of the Pharmacy Practitioners had good knowledge scores (71.95%). Meanwhile, the level of implementation of GCP has a good implementation value (82.92%). Good knowledge and implementation of Good Compounding Practice is very important to maintain the integrity and safety of drugs produced in compounding practices. This must be implemented in the training and education of pharmaceutical practitioners to help maintain the quality of safe and effective drug compounding practices.